EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DI SMA NEGERI 2 PADANG BOLAK - SABUNGAN SIREGAR; Muhammad Syahril Harahap; Anni Holila (JURNAL MathEdu (Mathematic Education Journal), 2019)
Abstract The aim of this study is to describe the effectiveness of applying cooperative learning of jigsaw type on students’ mathematical communication ability on the topic statistics at the eleventh grade students of SMA Negeri 2 Padang Bolak. This research was conducted by applying experimental (one group pre test post test design) with 47 students as the sample and they were taken by using total sampling technique . Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the average of applying jigsaw type was 3.56 (very good category) and (b) the average of students’ mathematical communication ability on the topic statistics before using jigsaw type was 58.81 (fair category) and after using jigsaw type was81.13 (very good category). Furthermore, based on inferential statistics by using pair sample ttest, and help SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, applying cooperative learning of jigsaw type on students’ mathematical communication ability on the topic statistics at the eleventh grade students of SMA Negeri 2 Padang Bolak. Keywords: cooperative learning of jigsaw type, mathematical communication ability